1997
DOI: 10.1212/wnl.48.5.1406
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging and transcranial magnetic stimulation

Abstract: Functional magnetic resonance imaging (fMRI) and transcranial magnetic stimulation (TMS) represent different approaches to mapping the motor cortex. fMRI identifies areas of hemodynamic changes during task performance while TMS provides electrophysiologic data concerning the localization and density of cortical motoneurons. Here we define the spatial correlation between fMRI and TMS maps and compared them with direct electrical cortical stimulation (ECS). We performed fMRI at 1.5 T on 3 normal subjects and 2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(37 citation statements)
references
References 0 publications
3
30
0
4
Order By: Relevance
“…Examples include the correlation between fMRI and positron emission tomography studies, the Wada test, transcranial magnetic stimulation, and direct electric cortical stimulation. [11][12][13][14] These data confirmed the ability of fMRI to localize and lateralize brain activity. Since both fMRI and TCD prove brain activity by means of changes in cerebral hemodynamics, we decided to validate fTCD with fMRI.…”
supporting
confidence: 56%
“…Examples include the correlation between fMRI and positron emission tomography studies, the Wada test, transcranial magnetic stimulation, and direct electric cortical stimulation. [11][12][13][14] These data confirmed the ability of fMRI to localize and lateralize brain activity. Since both fMRI and TCD prove brain activity by means of changes in cerebral hemodynamics, we decided to validate fTCD with fMRI.…”
supporting
confidence: 56%
“…In vitro experimental and modeling data suggests that the site of activation is predicted by the peak electric field magnitude (Amassian et al 1992;Maccabee et al 1993;Nagarajan et al 1993;Nagarajan and Durand 1995). Moreover, in vivo TMS experiments in both the motor and visual cortex have provided evidence that stimulation occurs at the location of the peak electric field (Wassermann et al 1996;Krings et al 1997;Boroojerdi et al 1999). Thus, even with minimal changes in the neural architecture (i.e., relative neural cell to current density orientations) current density magnitude attenuation seen with increasing atrophy should lead to an expected alteration in physiological (e.g., MEP, phosphene values) or behavioral (recovery from a given cognitive sequel) outputs in atrophic regions as compared to nonatrophic areas (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the present study was to investigate the occurrence of such repMNDs compared with other parameters of cortico-motoneuronal excitability. We Wrst compared stimuli given to the dominant versus the non-dominant hemisphere, since previous studies had indicated a greater excitability to (Brouwer et al 2001;Cantello et al 1992;Civardi et al 2000;De Gennaro et al 2004;Krings et al 1997;Netz et al 1995;Triggs et al 1999). We then attempted to actively manipulate the excitability of the cortico-motoneuronal pathway by two training regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the amount of repMNDs is probably inXuenced both at the spinal segmental level as well as supraspinally, but the contribution of either mechanism is also unclear (Z'Graggen et al 2005). It has been shown that motor evoked potentials (MEPs) elicited by stimulation of the dominant hemisphere are often larger than those after stimulation of the non-dominant hemisphere (Brouwer et al 2001;De Gennaro et al 2004;Netz et al 1995) and that cortical representation of the dominant hand is larger than the one of the non-dominant hand (Cantello et al 1992;Krings et al 1997;Triggs et al 1999). This asymmetry of the motor cortex seems not to be associated with functional diVerences in callosal inhibition (De Gennaro et al 2004;Civardi et al 2000).…”
Section: Introductionmentioning
confidence: 99%